The relationship between mother's knowledge and motivation with the regularity of ANC visits at the Muara Pinang Health Center, Empat Lawang Regency: Hubungan Pengetahuan dan Motivasi Dengan Keteraturan Kunjungan ANC di Puskesmas Muara Pinang Empat Lawang - Heni Angraini; Oktarina, Mika; Subani, Pitri; Eliagita, Choralina; Fivtrawati, Helleri (Jurnal Kebidanan Besurek, 2022)
This study aims to study the relationship between mother's knowledge and motivation with the regularity of ANC visits at the Muara Pinang Health Center, Empat Lawang Regency.This study uses a descriptive correlation approach with a cross sectional design. The population of this study were all postpartum mothers in the Muara Pinang Health Center Work area, Empat Lawang Regency in June-July 2021 as many as 30 people. Samples obtained as many as 30 people were taken by total sampling. Data collection is using secondary and primary data. Data analysis was carried out by using the Chi-Square test (χ2) and the Contingency Coefficient (C) test. The results obtained: (1) From the 30 samples there were 11 irregular ANC visits and 19 regular ANC visits; (2) Of the 30 samples, there were 8 people with poor knowledge, 10 people with sufficient knowledge and 12 people with good knowledge; (3) From 30 samples, there are 12 people with unfavorable motivation and 18 people with favorable motivation; (4) There is a significant relationship between knowledge and ANC visits in the Muara Pinang Health Center Work Area, Empat Lawang Regency, with a moderate relationship category and (5) There is a significant relationship There is a significant relationship between motivation and ANC visits in the Muara Pinang Health Center Work Area, Empat Lawang Regency, with a moderate relationship category